1998
DOI: 10.1002/(sici)1099-1174(199809)7:3<153::aid-isaf149>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

IN-QUOTES: a knowledge-based system for supporting decision making in weakly structured domains

Abstract: In complex and weakly structured domains, decision makers often employ multiple techniques, including quantitative modeling and reasoning from past experiences, to address the problem at hand. As such, there has been a call for more research on developing systems that merge problem‐solving approaches, such as reasoning from past experiences, with other paradigms to provide support for both the unstructured and structured aspects of the decision‐making process. Development of these systems is dependent on acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Research in expert systems applied to auditing (Eining et al, 1997; Massey & Brown, 1998) has shown that there is strong support for constructive dialogue used in expert systems as a means of encouraging their use in decision making (Eining et al, 1997). However, expert systems are best when used to support, rather than replace, the decision maker (Massey & Brown, 1998). In studies that relate learning and memory, Derry and Murphy made reference to the element of control in a description of their system that teaches problem‐solving ability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research in expert systems applied to auditing (Eining et al, 1997; Massey & Brown, 1998) has shown that there is strong support for constructive dialogue used in expert systems as a means of encouraging their use in decision making (Eining et al, 1997). However, expert systems are best when used to support, rather than replace, the decision maker (Massey & Brown, 1998). In studies that relate learning and memory, Derry and Murphy made reference to the element of control in a description of their system that teaches problem‐solving ability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We have used this iterative approach to the expert system design because the auditor's going-concern assessment represents a decision that must be made in a weakly structured domain. According to Massey and Brown (1998), one way to lend structure to this kind of weakly structured problem is through the use of a knowledge-based support system. As such, we recognize the limit of applying a rulebased decision process to the problem and are applying our expert system rule-base as a method to support the auditor's decision.…”
Section: Expert System Rule-basementioning
confidence: 99%